Social support buffers the effects of maternal prenatal stress on infants' unpredictability. (June 2021) - Takács, Lea; Štipl, Jiří; Gartstein, Maria; Putnam, Samuel P.; Monk, Catherine
Abstract: Objective: Exposure to stress in pregnancy has been shown to affect fetal development with short- and long-term physiological and behavioral consequences for the offspring. Although social support is known to lower perceived stress, no prior study has investigated the buffering role of social support in the context of prenatal stress effects on infant temperament. The aim of this study was to examine interactive effects of prenatal stress and social support on several dimensions of infant temperament at 9 months postpartum. Study design: A total of 272 mothers completed the Perceived Stress Scale and the Perceived Social Support Scale in the 3rd trimester of pregnancy. Infant temperament was assessed by mothers at 9 months postpartum using the Infant Characteristics Questionnaire. Linear regression models were performed to assess the effects of perceived stress, social support, and their interaction on infant temperament. Results: Prenatal stress interacted with social support, such that prenatal stress increased infant unpredictability when social support was below -0.5 SD. Conclusions: Prenatal stress was found to be a risk factor for infant temperamental unpredictability when combined with low social support perceived by the mother during pregnancy. Support of others, not previously examined in this context, can reduce the impact of prenatal stress. Highlights: No prior study has examined social support as a buffer for prenatal stress effects. Prenatal stress increased infant unpredictability only when social support was low. No effects of prenatal stress were found on infant overall difficulty.